The Broken Spell : Indian Storytelling and the Romance Genre in Persian and Urdu - Khan, Pasha M. (Book collections on Project MUSE., 2019)
Reconstructs Indian storytellers' lives and performance methods while recovering the marginalized worldview that popularized their art form.